Estimating the Shielding Requirements for a Newly Planned PET-CT Facility (Bangladesh Journal of Nuclear Medicine, 2019)
Positron Emission Tomography (PET) combined with Computed Tomography (CT) is a powerful and very sensitive diagnostic tool that integrates functional and anatomical imaging into one combined scanning system. Positron emission tomography is based on the characteristic way in which positrons annihilate by combining with an electron. This process usually results in the emission of two 511 KeV photons which travel in opposite directions. These 511 KeV annihilation photons are much higher energy than other diagnostic radiations. Because of this high energy of the annihilation radiation, shielding requirements for a PET facility are different from most of the other diagnostic imaging facilities and it’s a very important consideration in the design of a PET or PET-CT imaging facility. As a result, significant shielding may be required in floors and ceilings as well as adjacent walls in a PET-CT facility. In this work we present the estimation of the shielding requirements for a newly planned PET-CT facility. Shielding calculations of adjacent walls were presented for both controlled and uncontrolled areas. Formulas were used to calculate the shielding materials following the basic AAPM (American Association of Physicists in Medicine) guidelines. This mathematical analysis of the shielding estimation is very important for a newly planned PET-CT facility. Adequate safe planning with vendor, facility architect and a qualified medical physicist are essential to make a cost effective and safe design while maintaining radiation safety standards with regulatory limits.Bangladesh J. Nuclear Med. 21(2): 102-107, July 2018